Pengembangan Bahan Ajar Interaktif Berbantuan Aplikasi Book Creator dengan Model Problem Based Learning - Nisa, Sefiya Khoirun; Yohanie, Dian Devita; Darsono, Darsono (SJME (Supremum Journal of Mathematics Education), 2024)
The objective of this research is to develop interactive learning materials supported by the Book Creator application. Leveraging advancements in information technology is essential for enhancing interactivity in school learning processes. Book Creator facilitates the creation of interactive digital books for classroom use or independent study by students. The research employed a development method, or R&D, utilizing the 4D model. The research instrument uses a questionnaire and test. Expert assessments in media, material, and practitioner confirmed the product's validity with scores of 85.5%, 85%, and 92,3%, signifying a very high validity level. The practicality and effectiveness of the product is proven through testing on students. Average score of 89% from students in limited testing. Subsequent broader testing showed an average score of 86.7%, underscoring the material's practicality. Effectiveness is seen based on the increase in the number of students who have scores above the KKM with an initial percentage of 40% to 84%, indicating that teaching materials have effective criteria.